Social Action in the Movie Alkhallat+: Talcott Parson's Structural Functional Study - Ulfatil Mustafidah; Moh Zawawi (Universitas Cokroaminoto Palopo, 2024)
This research describes the results of the representation of social action in the film Alkhallat+ (2023) directed by Fahad Alammari and began airing on January 19, 2023 on Neflix. This research will provide an empirical understanding of the impact of actions taken in the social life of the community and contain the results of the representation of the form of social action. In the process of analyzing this research study, the researcher used the modern literary sociology approach of Talcott Parson's study with data collection techniques using listening and recording techniques in the Alkhallat + movie. The analysis of qualitative data is carried out by revealing the forms of social action using the AGIL scheme concept theory and interpreting the impact of social action into the classification of representation values. The findings of the data analysis of this social action research are in the form of 3 representation values classified into three parts, namely the representation of love, discrimination, and solving problems with the law. This study opens new insights related to the form of representation of social action, and provides a broader view of the concept of the AGIL scheme in the study of literary sociology for writers who want to conduct similar research or add new findings.